Calculation of polycondensation equilibria in aqueous solutions of silica and silicates - Maliavski, Nikolai; Zhuravlova, Olga (Eastern-European Journal of Enterprise Technologies, 2018)
We proposed some complication of the previously used calculation model to expand capabilities of the theoretical description of acid-base and polycondensation equilibria in water-silicate systems. A fuller account of the balance of Н+ ions enables the mathematical modeling of a structure and physicochemical properties of aqueous solutions not only of soluble silicates, but also of silicic acid, and with the same set of introductory thermodynamic parameters. The basis of the modified calculation model is a numerical solution of the system of eight linear and nonlinear equations by the Newton method. We used the new model to calculate parameters of the molecular mass distribution of silicon-oxygen species and pH value in aqueous solutions of silicic acid, as well as alkaline silicates and silicates of amines (amino silicates). We determined ranges of values of input thermodynamic parameters, which make possible self-consistent description of three non-trivial experimentally observed effects. These are a rheological anomaly in solutions of amino silicates, absence of this anomaly in solutions of alkaline silicates, and predominantly monomeric nature of silicic acid in a low-concentrated aqueous solution of silica. We showed that a self-consistent description of three effects is possible only if the sum of indexes of dissociation constants (pKa) and polycondensation constants (pKp) of a silanol group, is less than 11.6. We also calculated concentrations of hydrolytic and polycondensation structures in compositions of anions and cations for these solutions and analyzed dependences of these concentrations on parameters of the calculated model. In particular, we showed that the modification of the calculated model leads to a significant increase in calculated values of pH and a degree of dissociation of silanol groups for a silica solution, while the average degree of polymerization stays almost unchanged. In addition, we found that the degree of depolymerization of a siloxane bond may be nonmonotonically dependent on pKa value in solutions of amino silicates.